POLITIK HUKUM PIDANA Rekam Medis Sebagai Alat Bukti dalam Hukum Pembuktian Pidana - Marom, Ahmad Anfasul; Buamona, Hasrul (UIN Sunan Kalijaga Yogyakarta, 2015)
Medical Currently, the relationship between doctor and patient is not just the relationship treatment alone, but he is also part of